Variations in indwelling urinary catheter use in four Australian acute care hospitals. Issue 23 (30th September 2019) - Giles, Michelle; Graham, Laura; Ball, Jean; Watts, Wendy; King, Jennie; Bantawa, Kamana; Paul, Michelle; Harris, Alison; Paul O'Brien, Anthony; Parker, Vicki
Abstract: Aims and objectives: To identify the point prevalence of indwelling urinary catheters (IDCs) in adult inpatients in acute care hospitals, and to describe the indications for IDC insertion based on patient age, gender, specialty and hospital. Background: Catheter‐associated urinary tract infections (CAUTIs) are preventable healthcare‐associated infections. IDC duration is the strongest predictor of CAUTI, and little is known about characteristics of patients who receive an IDC. Design: Two single‐day point prevalence surveys collected baseline patient data as part of a larger pre‐post control‐intervention study. Methods: Surveys were conducted at four acute care hospitals in NSW, Australia, for all adult patients. Data collection included IDC presence, insertion details and urine culture collection. Point prevalence data were linked with electronically extracted patient demographic data. This study is presented in line with STROBE checklist (See Supplementary File 1 ). Result: Data from 1, 630 patients were analysed, with 196 patients (12%) identified as having an IDC on the survey dates. IDC prevalence rates were higher in males (13%) than in females (11%). Critical care had the highest rate of patients with IDCs (42%). Urine cultures were collected in 70 patients with an IDC (43%). Conclusions: Findings indicated similar rates of IDC use in males and females, and there was no significant difference in age between patients with or without an IDC. However, indication for IDC varied by patient age and gender. High rates of urine culture collection may represent routine collection. Relevance to clinical practice: IDC use is found across genders, all age groups and specialties. Nurses should be aware that any of their patients may have an IDC and be particularly aware of certain indications based on patient age and gender. Routine urine culture collection is not advised, and instead, nurses should be guided by clinical decision‐making tools.